2018
DOI: 10.7759/cureus.3809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Health Education on Dengue Fever: A Comparison of Knowledge, Attitude, and Practices in Public and Private High School Children of Jeddah

Abstract: Objective More than half of the world’s population live in areas with a potential risk of acquiring dengue fever (DF). Health education interventions are effective, barring a language communication gap. The objective of this study was to estimate the effect of health education in the knowledge, attitude, and practices (KAP) towards DF control and prevention in public and private schools. Materials and methods We assessed the DF control and prevention strategy KAP of students of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 13 publications
4
16
0
2
Order By: Relevance
“…In contrast, other studies of healthy adults in Indonesia [ 13 ] and Columbia [ 40 ] reported that dengue experience is associated with attitudes towards dengue prevention. Changing attitudes towards health remain an issue; although school-based health education was utilized, children's attitudes towards the disease did not improve [ 34 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies of healthy adults in Indonesia [ 13 ] and Columbia [ 40 ] reported that dengue experience is associated with attitudes towards dengue prevention. Changing attitudes towards health remain an issue; although school-based health education was utilized, children's attitudes towards the disease did not improve [ 34 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…These changes are consistent. Health education that is given repeatedly over a long enough period influences the community's understanding of DHF and its transmission risk factors [3], [59], [60]. DHF is a disease that is often neglected [18], especially at this time when most people are focused on efforts of COVID-19 control, including in Indonesia.…”
Section: Discussionmentioning
confidence: 99%
“…Dengue awareness education among school and college students can assist in preventing the outbreak of dengue-borne diseases. The role of education in dengue transmission has been well-documented in the literature [28,38]. Moreover, due to inadequate financing in most of developing countries, education about dengue is not provided by formal means but through informal modes, such as verbal awareness or, to some extent, distribution of leaflets, posters or recorded material.…”
Section: Discussionmentioning
confidence: 99%